Information Strategies – Evolution and Influence to the Knowledge - Akrap, Gordan (Array, 2014)
What we investigate in this paper is a theoretical frame common to disciplines that research form of public knowledge, respectively common methodological approach to a series of activities that aim is not only to form public knowledge, but also have a the duty to provide information superiority. The proposed theoretical approach enables understanding and interpretation of the impact of modern information strategies (information and media operations (IO, MO)) on corpuses of public knowledge. IO and MO are focused on specific cognitive domains of target audience, and the effects of such formed information and communication systems have a direct effect on the organization of the targeted corpuses of (public) knowledge. Low intensity conflicts (LIC) become the dominant form and way of dealing with international and local threats. The articulation of national information strategies should ensure political, economic, cultural and military domination of the actors on the global scene. National, as well as business, information doctrines and strategies define offensive and defensive methods and techniques of usage of information resources with aim to ensure information superiority. Superiority in weapons and lethal means is replaced by the superiority in the information and technical and technological development. Superiority in controlling and monitoring of the battlefield turned into a superiority and control of the media space. Battlefield is no longer dependent on space and time. Battlefields are media, and ICT space in which different IO/MO can last for 24 hours a day, 7 days a week, 12 months a year.